Effect of basicity on the morphologies of ZnO produced using a sonochemical method - Thongtem T. (2014)
Wurtzite ZnO was produced by the sonochemical reactions of 0.005 mol Zn(NO3)2 and different moles of NaOH in de-ionized water. The phase was characterized using X-ray diffraction (XRD) and selected area electron diffraction (SAED). A Raman peak was clearly detected at 435 cm-1. The SAED patterns were in accordance with those of the simulation. Scanning and transmission electron microscopies (SEM and TEM) revealed the presence of 72 ± 17 nm nano-particles, and nano-plates and spear-shaped particles in flower-like clusters, influenced by basicity conditions. By using high-resolution TEM (HRTEM), a spear was observed growing in the [0 0 1] direction normal to its (0 0 2) plane. © 2009 Elsevier B.V. All rights reserved.